THE APPROACH OF EXAMPLES NON EXAMPLES METHOD WITH IMAGE MEDIA TO IMPROVE STUDENTS’ WRITING SKILLS AT GRADE 2 OF SDN 022 HARAPAN BARU INDRAGIRI HILIR - Rodiyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This form of research was a class action study conducted at grade 2 of SDN 022 Harapan Baru Kabupaten Indragiri Hilir conducting in 2 cycles. Cycle I was planning and Cycle II was actions using examples non examples approach with image media. The study subject consisted of 16 grade 2 students. The research instruments were observation sheets and daily test sheets. The purpose of the research was to improve the students’ writing skills at grade 2 of SDN 022 Harapan Baru. The results showed a significant improvement both in terms of teacher’s and students’ learning activities as well as the students' writing skills. The observation of teacher’s activity in the initial data obtained a percentage of 55%. Then, after the reflection of learning, the percentage increased to 85% with good category. The observation of students’ activity in the initial data obtained a percentage of 53% with fairly good category. After the reflection of learning the percentage was 92% with good category. After that, the results of the student's writing ability found an average score of 60 in the preliminary data. After the reflection of learning, the average score was 88. Based on the presentation, it was concluded that examples non examples learning methods using image media improved the students’ writing skills at grade 2 of SDN 022 Harapan Baru.